Nurses' harm prevention practices during admission of an older person to the hospital: A multi‐method qualitative study. (7th July 2022) - Redley, Bernice; Douglas, Tracy; Hoon, Leonard; de Courten, Barbora; Hutchinson, Alison M.
Abstract: Background: Nurses' harm prevention practices during the admission of older persons to hospital have important consequences for patient safety, preventable patient harm and length of hospital stay. Novel solutions are needed to assist nurses to balance complexity, high workload burden and patient safety during admission processes. Aim: Explore the nurses' experiences of harm prevention practices during the admission of an older person to the hospital. Design: A multi‐method qualitative study informed by frameworks of behaviour change and human‐centred co‐design. Methods: The purposive sample included 44 nurses, 5 clinicians from other disciplines and 3 consumers recruited from five general medicine wards across three hospitals of a large public health service in metropolitan Melbourne, Australia. Data were collected over 12 h of naturalistic observations of nurses during eight patient admissions, and during four participatory human‐centred co‐design workshops between August 2019 and January 2020. Observation, field notes and workshop artefact data were integrated for qualitative content and thematic analysis. Results: Analysis revealed a 5‐step journey map, with a temporal logic, that captured nurses' experiences, as well as the enablers and barriers to harm prevention practices when admitting an older person to the hospital. The consensus was reached on three priority features to assist nurses to implement harm prevention practices when they admit an older person to the hospital: (1) prioritize important care; (2) tailor care to the individual and (3) see the big picture for the patient. Conclusion: The novel research approach identified five steps in nurses' activities and harm prevention practices during admission of an older person to the hospital, and key features for a solution to assist nurses to keep patients safe. The findings provide the foundation for further research to develop interventions to assist nurses to manage high workloads during this complex activity.